Upaya Pengembangan Desa Wisata Berbasis Sustainable Tourism di Desa Barania, Kecamatan Sinjai Barat - Fadillah, Andi Sarkiah; Rosnani, Rosnani (Universitas Bosowa, 2024)
The purpose of this research is to determine the efforts made by the government of Barania Village in developing the tourism potential it has into a sustainable tourism village which can support the achievement of the Sustainable Development Goals (SDGs). This research uses descriptive research with a qualitative approach aimed at providing a clear description and explanation of the efforts and strategies of the government of Barania Village in developing sustainable tourism villages while considering indicators of sustainable development. Data collection techniques in this research include observation, interviews, documentation, and literature review. The results of this study show that in implementing sustainable tourism village development, the government of Barania Village has implemented several strategies in utilizing and managing natural resources, structured fund allocation, using technology and information to promote Barania tourism village, and providing facilities and infrastructure. In addition, community involvement in the development of tourism villages is a necessity because the participation of the community from the planning stage to management can accelerate the achievement of sustainable development goals, especially in improving the welfare of village communities in various aspects of life. The expected outcome of this research is to provide an overview of the efforts and strategies carried out by the government of Barania Village in developing the potential of sustainable tourism villages that can support the acceleration of achieving sustainable development goals.